ICT in Indonesian Public Secondary Schools: EFL Teachers’ Attitude and Problems - Eddy Haryanto (Edukasi, 2021)
Teachers’ attitude toward technology in the classroom plays a significant role to achieve educational goals; this mixed-method study investigates the attitude and problems of secondary school English teachers toward ICT in English teaching. Data of this study were collected from the questionnaire with forty-six English teachers and interviews with five teachers from eleven public secondary schools in Jambi city. The findings indicate teachers have a positive attitude toward the use of ICT. Meanwhile, the problems show that the overall mean rating was 3.11 (uncertain), which means English teachers could not determine whether they encountered problems or not in using ICT in teaching English. However, qualitative results showed that the problems faced by teachers were a lack of funds and support for training from the government.